(untitled) (Fiep Bulletin - online, 2012)
Aging brings changes in cardiorespiratory system, like the reduction in respiratory muscle strength (RMS). The aim of this study was to evaluate the respiratory muscle strength in healthy elderly active and sedentary people. It was evaluated 66 old females, 36 of those make exercises regularly (at least 3 times a week) and 30 are sedentary, all of them between 60-81 years. It was used a spirometry test to demonstrate the well function of the lung. The RMS was evaluated by the maximal lung pressures with a digital manovacuometry. The student t test to comparison between groups and Pearson correlation test were used (p<0.05). The maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) were significantly higher in the active group in all age groups evaluated: 60-69 years [active group versus sedentary: MIP = 132,84 + 32,83 ?52,91 + 21,31 cm H2O; MEP = 155 + 26,48 ? 76,25 + 24,51 cm H2O]; 70-81 years [active group versus sedentary: MIP = 124,05 + 36,25 ? 44,11 + 19,58 cm H2O; MEP = 143,76 + 33,12 ? 69,38 + 19,32 cm H2O] p=0,00. The respiratory muscle strength (MIP and MEP) obtained in the active group was higher than that reported by Neder et al. (1999). The practice of regular exercise resulted in a higher RMS in people above 60 years old in relation to sedentary people with the same age group.